2016
DOI: 10.1167/iovs.15-18010
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Intravitreal Gas Bubbles at Risk of High Intraocular Pressure Without Exceeding Elevation of Surgery: Theoretical Analysis

Abstract: In our simulations the change of bubble size outpaced the change of aqueous humor volume resulting in a 2-fold risk to patients. First, the bubble size reduction at the low elevation may increase the risk of ocular hypotony and postsurgical retinal detachment. Second, the combined increasing bubble size and accumulated aqueous humor puts patients at risk of high peak IOP after ascent even without exceeding the surgical elevation. The risks are primarily dependent on rates of elevation change and duration spent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Recently, case reports and our theoretical models have shown that even if the patient travels to a low altitude and subsequently returns to the initial elevation (without ever exceeding the initial elevation), the peak IOP values may surpass the normal values 11,12. As such, we have demonstrated that the change in altitude (and not necessarily the absolute height of the elevation) can lead to high values for the IOP.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…Recently, case reports and our theoretical models have shown that even if the patient travels to a low altitude and subsequently returns to the initial elevation (without ever exceeding the initial elevation), the peak IOP values may surpass the normal values 11,12. As such, we have demonstrated that the change in altitude (and not necessarily the absolute height of the elevation) can lead to high values for the IOP.…”
Section: Introductionmentioning
confidence: 50%
“…In this investigation, we chose five subsea tunnels as case studies of typical transportation methods that may put patients with intravitreal gas bubbles at risk for ocular hypotony. While previous studies were conducted to investigate the potential for dangerous peak values of IOP induced by changes in elevation,5,7,9,11,12,14,15 to our knowledge, the occurrence of ocular hypotony in the presence of intravitreal gas bubbles has not yet been studied. In our assessment of the changes in IOP during travel through these five subsea tunnels, we also investigated how the occurrence of ocular hypotony can be influenced if model parameters such as aqueous humor filtration or production rates are decreased/increased from their base mean values.…”
Section: Introductionmentioning
confidence: 99%
“…163 Care must also be taken when traveling to lower elevations because reduction in bubble size may increase the risk of ocular hypotony and postsurgical retinal detachment. 164 Intraocular gas also limits the type of anesthetic agents that can be used. Most surgeons require their patients to wear a wristband warning alert that states that the wearer's eye contains intraocular gas and that anesthetic (e.g., nitrous oxide) should be avoided.…”
Section: (I+ Good Quality Discretionary Recommendation)mentioning
confidence: 99%
“…The use of nitrous oxide in a patient with intraocular gas may result in a dangerous rise in IOP. 164 Patients who have surgery are usually examined the first 1 to 2 days post-operatively and again approximately 1 to 2 weeks following surgery. The frequency and timing of Ocriplasmin is a recombinant protease that was approved by the FDA in 2012 for the management of symptomatic VMA.…”
Section: (I+ Good Quality Discretionary Recommendation)mentioning
confidence: 99%
“…), this trend is likely to accelerate even more in the coming future. In addition, computer programing has become an essential part of data analysis [2][3][4] and simulation 5,6 in biomedical research. As interacting with computing-enable devices becomes easier and more prevalent, it is possible that engineers will graduate with the ability to quickly navigate user interfaces but without a detailed, theoretical knowledge of computing fundamentals.…”
Section: Introductionmentioning
confidence: 99%